Tracheal intubation in patients with Pierre Robin sequence: development, application, and clinical value based on a 3-dimensional printed simulator - Mao, Yu; Liu, Lu; Zhong, John; Qin, Pei; Ma, Rui; Zuo, Mingzhang; Zhang, Li; Yang, Lifang (Frontiers in Physiology, 2024)
Background: The main clinical manifestations of patients with Pierre Robin sequence (PRS) include micrognathia, the glossoptosis and dyspnoea. The difficulty of tracheal intubation (TI) in such patients is increased. Objective: The purpose of the study was to evaluate the reliability and efficacy of the PRS simulator. Methods: A PRS simulator was developed by using 3-dimensional (3D) printing technology under computer-aided design. A total of 12 anaesthesiologists each trained 5 times for TI on the PRS Training Simulator-1 and recorded the simulation time. After the training, they were randomly divided into three groups with a total of 12 nontrained anaesthesiologists, and the simulation was completed on PRS Simulator-2, 3 and 4. The simulation time was recorded, and the performance was evaluated by three chief anaesthesiologists. Then, all 24 anaesthesiologists completed the questionnaire. Results: A PRS simulator developed by 3D printing was used to simulate the important aspects of TI. The average number of years worked was 6.3 ± 3.1 years, and 66.7% were female. The time for the 12 anaesthesiologists to complete the training gradually decreased (p < 0.01). Compared with the trained anaesthesiologists, the simulation time of TI in the nontrained anaesthesiologists was much longer (all p < 0.01). In addition, the simulation performance of the trained anaesthesiologists was relatively better (all p < 0.01). Conclusion: The reliability and efficacy of the PRS simulator is herein preliminarily validated, and it has potential to become a teaching and training tool for anaesthesiologists.